Constitutional Deference, Courts and Socio-Economic Rights in South Africa - Kirsty McLean (Pretoria University Law Press (PULP), 2009)
Constitutional Deference, Courts and Socio-Economic Rights in South Africa by Kirsty McLean 2009 ISBN: 978-0-9814124-8-1 Pages: viii 246 Print version: Available Electronic version: Free PDF available